Personal financing without interest: a comparison between Bay Al Inah and Qardhul Hasan - Mohamad, Amri; Hassan, Othman Zailani; Abul Hasan Ashari, Anis; Saidi, Noraida (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2024)
Islamic contracts are different from the conventional loan contracts. The primary differences are that Islamic contracts avoid interest (riba), uncertainties (gharar), gambling (maysir), and other non-shariah compliant activities. These are the practices being used in Islamic Financial Institutions (IFI), not only in Malaysia but also in other parts of the world. The prohibition of riba has been clearly mentioned in the Quran, for example; “O believers! Do not consume interest, multiplying it many times over. And be mindful of Allah, so you may prosper.” (“Hai orang-orang yang beriman, janganlah kamu memakan riba dengan berlipat ganda dan bertakwalah kamu kepada Allah supaya kamu mendapat keberuntungan.”) (“…Allah telah menghalalkan jual beli dan mengharamkan riba.”) In Islamic contracts, each of the components involved, from input to output, must adhere to shariah principles. This means that if a gambling company wants to deposit its gambling money into the IFI, then that money will not be accepted. Likewise, if a borrower wants to borrow money for non-shariah compliant activities, then that loan will not be approved by the IFI. Not only does the input (deposit) and output (lending) need to comply with shariah, the processes within the IFI itself must also comply with shariah. The most prominent distinction between Islamic loan contracts and conventional loan contract is that in the former, there will not be any element of interest at all whereas in the latter, interest will become the central figure.